Tatar folk festivals and traditions through the eyes of a historian. To the 155th anniversary of scholar G.N. Akhmarov. - Elmira K. Salakhova (Историческая этнология, 2019)
The name of Gaynetdin Nedzhmutdinovich Akhmarov (1864–1911) holds a spe-cial place among the scholars of the early 20th century due to his significant and multi-dimensional work. He is an educator, author of textbooks, historian, ethnographer, and public figure. The purpose of the paper is to explore the description of traditional Tatar customs and holidays in G.N. Akhmarov’s works. His historical analysis and explana-tion of the origin and development of folk traditions generates big interest not only in the academic circles, but among a broad audience of readers. The scholar’s works con-tain богатый материал on Tatar festivities. One particular work explores a Tatar wed-ding, which is shown as a national custom that has been formed over the course of many years. In his description of a Tatar wedding, the author provides its historical justification as he relies on his vast knowledge of history. G.N. Akhmarov uses this approach in the analysis of the Tatar holiday Sabantuy. The scholar reveals its history and conducts a comparative historical analysis with holidays of other Turkic peoples. The article exa¬mines the researcher’s view on other traditional festivities of Tatars.